Project management jumpstart - Heldman, Kim (Indianapolis : Sybex, a Wiley brand, 2018)
Includes an exploration of current best practices, this book offers a clear, practical introduction to the complex world of project management, with an entertaining approach based on real-world application.
Chapter 1: Building the foundation -- Chapter 2: Developing project management skills -- Chapter 3: Initiating the project -- Chapter 4: Defining the project goals -- Chapter 5: Breaking down the project activities -- Chapter 6: Planning and acquiring resources -- Chapter 7: Assessing risk -- Chapter 8: Developing the project plan -- Chapter 9: Budgeting 101 -- Chapter 10: Executing the project -- Chapter 11: Controlling the project outcome -- Chapter 12: Closing the books -- Appendix A: Answers to review questions -- Appendix B: Sample project management forms and checklists.
Includes bibliographical references and index.
Produced by the publisher.
Held by CAPER-BC, Langara College.
John Wiley and Sons
Keywords: Project management; Gestion de projet; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Project management